Iron metabolism and diagnostic of iron deficiency in inflammatory bowel diseases. - T. Boyko (Medičnì Perspektivi, 2013)
According to WHO data about 2 billion people in the world suffer from anemia, that is 1/3 of the whole population of the planet. Causes of anemic states are varied and often they complement each other, iron deficiency anemia (IDA) which occurs in 75-80% of cases is of the greatest significance among anemias of different origins. Anaemia is a frequent systemic manifestation of inflammatory bowel diseases (IBD) which significantly worsens quality of life, it is associated with disease severity and resistance to therapy. The article highlights pathogenesis and diagnosis of anaemia in IBD patients based on current understanding of iron homeostasis in chronic inflammation. 69 anemic patients with IBD compared to with 30 patients with normal Hb level were under investigation. The control group consisted of 15 healthy individuals. The examination included total blood count, parameters of iron metabolism (serum iron, unsaturated and total iron binding capacity, trasferrin saturation, ferritin), as well as hepcidin-25 level and erythropoetin in serum. Depending on sTfR/log ferritin index the patients were divided into groups:  44% with IDA, 34 % – anemia of chronic disease (ACD) and 22 % – combination of IDA and ACD. A significant decrease of hepcidine-25 level in serum of IDA patients and increase of that one against inflammatory process in patients with ACD and ACD+IDA was found being. An increase of erythropoetin production was established in anemic patients, less expressed on ACD background.